(untitled) (Web of Humanities: Journal of Social Science and Humanitarian Research, 2024)
Color imaging has undergone a fascinating evolution, tracing its origins back to ancient times when early civilizations experimented with natural pigments to create colorful artworks. However, it wasn’t until the 19th century that significant advancements in color reproduction techniques emerged, with pioneers such as James Clerk Maxwell and Thomas Sutton laying the groundwork for modern color photography. This article explores the journey of color imaging, from the discovery of additive and subtractive color mixing principles to the development of innovative technologies like the three-color process and Kodachrome film. Furthermore, it delves into the digital era, highlighting the revolution brought about by digital sensors and image processing algorithms, which have democratized color photography and transformed the way we capture, manipulate, and perceive color images in the modern age.